A Comprehensive Review on Risk Factors Affecting the Crash Severity - Milad Safari; Seyed Shamseddin Alizadeh; Homayoun Sadeghi Bazargani; Atefeh Aliashrafi; Azam Maleki; Parosa Moshashaei; Mohammad Shakerkhatibi (Iranian Journal of Health, Safety and Environment, 2020)
As a matter of growing machinery life, traffic crashes are considered an inevitable source of injuries and costs around the world. Regarding to increasing traffic accident outcomes, controlling the current status is necessary. In this way, identifying risk factors affecting the crash severity is an essential step toward initiating a convincing solution. The core objective of this study was to categorize the risk factors affecting the severity of crashes. Data needed for this study were gathered through searching Web of Science, Google Scholar, and Science Direct databases using the keywords included fatal and crash, injuries and crash, fatal and traffic accident, and injuries and traffic accident. Based on 83 selected studies for review, factors affecting the crash severity divided into five factors and forty-seven sub-factors. The most prevalent sub-factors were age, sex, safety belts, alcohol and drug use, speed, weather conditions, lighting conditions, time of the day and week, vehicle kind, road condition, collision type and crash location. Many risk factors affect crash severity and determination of the most important ones can be a prelude in reducing the effects. Therefore, the conclusion of this review can assist to traffic safety experts, police and contribute to distinguishing and monitoring the risk factors affecting crash severity transportation agencies.